Influência do ambiente de cultivo em acessos de erva-baleeira (Varronia curassavica Jacq.) - Silva, Jefferson Henrique Santos (2017)
Varronia curassavica is a Brazilian native medicinal plant, popularly known as “erva-beleeira”, that belong to the Cordiaceae family, and can be found in the coastal strip from the state of Ceará to the state of Rio Grande do Sul. The objective of this work was to evaluate the influence of the cultivation environment on the anatomical, physiological and essential oil characteristics of V. curassavica accessions. The experimental design was in randomized blocks, in a split plot scheme, testing two cultivation environments (full sun and protected with 50% shade screen) in the plots, and five V. curassavica accessions (VCUR-101, VCUR-102, VCUR-201, VCUR -302 and VCUR-802) in the split plots, with three replications and three plants per replication. At 180 days of cultivation, foliar anatomy, chlorophyll a, b and, total, leaf area, dry weight of plants, and content, yield and chemical composition of the essential oil were evaluated. The thickest palisade parenchyma were registered in VCUR-102 (75.87 μm), in full sun environment, and VCUR-201, in both environments (75.87 and 54.75 μm). The thickest adaxial epidermis were found in the accessions VCUR-102 and VCUR-201 (21.15 and 13.60 μm), in full sun and protected environment with 50% shade screen, respectively. The accession VCUR-802 presented the largest leaf area (18.30 cm2) in the protected environment with 50% shade screen. The essential oil content of the accessions ranged from 1.33 to 3.9% in full sun environment, and from 1.4 to 3.3% in the protected environment with 50% shade screen. The essential oil yield of the accessions ranged from 0.26 to 0.87 mL.plant-1 in full sun environment, and from 0.34 to 0.53 mL.plant-1 in the protected environment with 50% shade screen. The highest contents of trans-caryophyllene (17.9%), α-humulene (5.11%), germacrene D (4.86%) and α-zingiberene (38.04%) were found in plants of accession VCUR-302 cultivated in protected environment with 50% shade screen. Cultivating V. curassavica for 180 days in full sun environment provided bigger development of leaf limb, palisade parenchyma and epidermis of the abaxial and adaxial face in almost all the tested accessions. In general, the full sun environment also favored the higher production of dry mass, and essential oil content and yield.